2016
DOI: 10.1021/acs.jmedchem.5b01850
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship of 18F-Labeled Phosphoramidate Peptidomimetic Prostate-Specific Membrane Antigen (PSMA)-Targeted Inhibitor Analogues for PET Imaging of Prostate Cancer

Abstract: A series of phosphoramidate-based prostate specific membrane antigen (PSMA) inhibitors of increasing lipophilicity were synthesized (4, 5, and 6), and their fluorine-18 analogs were evaluated for use as positron emission tomography (PET) imaging agents for prostate cancer. To gain insight into their modes of binding, they were also cocrystallized with the extracellular domain of PSMA. All analogs exhibited irreversible binding to PSMA with IC50 values ranging from 0.4 to 1.3 nM. In vitro assays showed binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…An irreversible binding profile is desirable because it might induce a higher rate of internalization than weaker interaction and consequently, rapid in vivo tumor uptake after the administration and greater contrast with the background tissues [ 42 ]. Conversely, reversible binding may explain the tumor washout over several hours observed with urea-based inhibitors [ 43 ].…”
Section: Glutamate-phosphoramidate Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…An irreversible binding profile is desirable because it might induce a higher rate of internalization than weaker interaction and consequently, rapid in vivo tumor uptake after the administration and greater contrast with the background tissues [ 42 ]. Conversely, reversible binding may explain the tumor washout over several hours observed with urea-based inhibitors [ 43 ].…”
Section: Glutamate-phosphoramidate Inhibitorsmentioning
confidence: 99%
“…A series of FB ring-containing compounds derivative of CTT1057 were designed in order to further understand the SAR of phosphoramidates respect to the interactions within the ABS and to evaluate their corresponding in vivo pharmacokinetics and biodistribution [ 43 ].…”
Section: Glutamate-phosphoramidate Inhibitorsmentioning
confidence: 99%
“…Additionally, it facilitates the engagement of these moieties with structurally defined pockets in the entrance funnel (e.g., the S1 accessory hydrophobic pocket or the arene-binding site), thus contributing to the increased affinity of such bivalent ligands for PSMA ( Fig. 6) and allowing for the structure-assisted design of the next generation of ligands (48,(51)(52)(53)(54)(55).…”
Section: Lesson 2: Need For Structure-aided Design Of Glu-ureido-basementioning
confidence: 99%
“…Contrary to other PSMA targeting compounds, which are urea-based, [ 18 F]F-CTT1057 is a phosphoramidate-based PSMA inhibitor. This compound resulted from a series of derivatives which differ in the linker between binding sequence and 4-[ 18 F]fluorobenzoyl group [171]. A preliminary study with patients showed a low radiation burden as well as similar distribution as found for urea-based analogues like [ 18 F]F-DCFPyL [166].…”
Section: Prostate-specific Membrane Antigenmentioning
confidence: 99%